SIMULTANEOUS EVALUATION OF ABACAVIR SULFATE AS WELL AS LAMIVUDINE IN MEDICAL FORMULATIONS BY GRADIENT REVERSED-PHASE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY TECHNIQUE - K, ALEKHYA; Ms, Srinivasan; S, SUBRAMANI; R, SURYA; M, VIJEY AANANDHI (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: A precise, accurate, simple, and gradient reversed-phase high-performance liquid chromatography (HPLC) method was adapted for the determination of abacavir sulfate (ABV) in combination with lamivudine (LMV) having tablet formulations simultaneously. This method developed has been validated as per the guidelines of ICH. Method: Waters HPLC has been used in the method with a column named Zorbax C18 with the dimensions as 4.6 nm×150 mm, 3.5 μm. Phosphate buffer (PH - 3.9) was used as Eluent - A, Eluent - B was methanol, and water and methanol (50:50 v/v) were utilized as diluents. The rate of flow was 1.5 ml/min. Results: The wavelength of detection has been detected at about 270 nm. Linearity ranges of ABV and LMV were 88–266 μg/ml and 38–116 μg/ml, respectively. Retention times of ABV (3.66 min) and LMV (10.71 min) were determined. The values of the study of percentage recovery of ABV and LMV were determined to be within 98.3–99.2%. Conclusion: The estimation of ABV and LMV in all pharmaceutical dosage forms could be performed successfully by employing this method.